Differences in Anthropometric Characteristics among Junior Soccer and Basketball Players - Spasoje Spaic; Velisa Vukasevic; Bojan Masanovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
The aim of this study was to obtain the relevant knowledge about significant differences in some anthropometric characteristics of junior soccer and basketball players. The sample included 38 male subjects divided into two subsamples. The first subsample included 25 subjects, who rain in the junior selection in the Football club Vojvodina from Novi Sad, while the other subsample included 13 subjects who train in the junior selection in the Basketball club Vojvodina, from Novi Sad. The variables sample included 20 anthropometric measures that defined longitudinal and transversal dimensionality of skeleton, volume and mass of the body, and subcutaneous adipose tissue. The results were analysed in a statistical procedure marked as a significance testing of two arithmetic means of the independent samples, a t-test at the level of significance of p<0.05. It was concluded, based on these results, that significant differences occur in body height, bodyweight, elbow diameter, wrist diameter, lower arm circumference (max), lower leg circumference (min) and lower leg circumference (max), while the significant difference does not occur in knee diameter, ankle joint diameter, upper arm circumference (min), upper arm circumference (max), lower arm circumference (min), upper leg circumference (min), upper leg circumference (max), upper arm skinfold, lower arm skinfold, thigh skinfold, calf skinfold, chest skinfold and abdomen skinfold.